2013
DOI: 10.4028/www.scientific.net/amr.838-841.2449
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Tetraploid of a Yellow Flesh Mini-Watermelon Using Oryzalin

Abstract: In order to provide parent material for small-type triploid watermelon, this study has been carried out to induce high-quality tetraploid watermelon. We induced tetraploid plants of watermelon by treating the growing points of seedlings of a small-type yellow flesh diploid watermelon with 40, 60 and 100ml/L Oryzalin for different treating time. The autotetraploid plants were selected and identified basing on morphology, determination of the number of chloroplasts in stomatal guard cells, flow cytometry analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Consistent with our results, an increase in the number of chloroplasts per guard cell has been reported in tetraploid watermelons (Şimşek et al, 2013;Zhang et al, 2014). A similar increase in the chloroplast number in guard cells from 7.6-8.1 chloroplast/stoma to 17.7-18.8 chloroplast/stoma was also reported by Oh et al (2015a) in watermelon.…”
Section: Stomatal Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our results, an increase in the number of chloroplasts per guard cell has been reported in tetraploid watermelons (Şimşek et al, 2013;Zhang et al, 2014). A similar increase in the chloroplast number in guard cells from 7.6-8.1 chloroplast/stoma to 17.7-18.8 chloroplast/stoma was also reported by Oh et al (2015a) in watermelon.…”
Section: Stomatal Analysissupporting
confidence: 93%
“…Flow cytometry allows polyploid plants to be analysed at an early stage, saving space and time (Väinölä, 2000). Zhang et al (2014Zhang et al ( , 2019 reported that the fluorescence intensity of the main peak of the diploid E46 watermelon genotype is 203.46 pg/2C, and the fluorescence intensity of the main peak of the tetraploid E46 watermelon genotype is about 371.07 pg/2C, which means that the DNA content of cells of tetraploid plants is about twice that of diploid plants. This result is in consensus with our fluorescence intensity results.…”
Section: Stomatal Analysismentioning
confidence: 99%
“…The material is homologous diploid (E46, 2n) and tetraploid (yE46, 4n) watermelon. Tetraploid watermelon is induced by homologous diploid watermelon by colchicine (Sigma Chemical Company, MO, USA) [36], the diploid drying seeds were soaked in warm water at 50 °C for 30 min, soaked in 0.5% KMnO 4 (Sinopharm Chemical Reagent Company, Shanghai, China) for 30 min, then washed with water and soaked in water for 6 h. Germination at 28 °C for 24–36 h. Seeded in a 72-well format tray (Grass soil:Perlite = 3:1), 25 °C. When the cotyledons of the seedlings were flattened, the new leaves of the growing point were removed, and the growth point was treated with a 0.3% colchicine, which was treated twice every day at 8:00 and 18:00 for 7 days.…”
Section: Methodsmentioning
confidence: 99%